Entre a falta de alimentação e o não cumprimento de prazos: um estudo empírico sobre os fluxos de atendimento e encaminhamento de adolescentes em conflito com a lei na 90ª Delegacia de Polícia de Caruaru-PE. - Souza, Edivan Cordeiro de (2022)
This research sought to understand the service and referral flows of adolescents in conflict with the law at the 90th Police Station (on duty) of Caruaru/PE. The aim was to reveal the types of violation of rights borne by adolescents since their arrival at that police station all the way through the procedure for drawing up the arrest and/or release report. The hypothesis was that adolescents are being treated as adult prisoners when apprehended in flagrante delicto, and taken to a common police station, that is, a non-specialized one, which results in violations of several human rights. In this way, the literature on the development of children’s and adolescents’ rights in Brazil was used as a starting point and, along with the teachings of critical criminology, formed this dissertation’s theoretical framework. Methodologically, this was an empirical, qualitative research that allowed for the mapping of these adolescents’ profiles, and, through ethnography, the examination of the day-by-day reality found in the research site in what refers to their arrest and referral to other services. It exposes the role of the police and their practical knowledge regarding adolescents in conflict with the law, as well as acknowledges the difficulties faced in the context of public security in Brazil. In conclusion, it was found that adolescents that are arrested at the time of the offence and taken to the 90th Police Station in Caruaru have their rights violated, particularly due to the lack of adequate spaces and specialized police (services). The lack of a police station specialized in adolescents in conflict with the law leads to a practical reality that is far from what is foreseen in Brazil’s Child and Adolescent Statute, as the rights to freedom and respect for their dignity as humans in development and as subjects of rights are ignored.